IMPLEMENTASI PEMBELAJARAN INTERAKTIF MATERI BUKU BESAR TERHADAP SISWA DI SMA SANTO KRISTOFORUS 2 - Annastasha Geraldine; Emillia Satrasasmita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2026)
Teaching Assistance activities within the Merdeka Belajar Kampus Merdeka (MBKM) program serve as a tangible form of collaboration between higher education institutions and schools. This program provides an opportunity for university students to be directly involved in the teaching and learning process at schools, allowing them to apply the knowledge they have acquired while developing professional teaching skills. The main objective of this activity is to enhance students’ teaching competence and assist high school students in understanding learning materials in a more engaging and comprehensible manner. In its implementation, the teaching assistance program focused on the topic of the general ledger for Grade XII students at SMA Santo Kristoforus 2, which is often considered challenging due to its requirement for accuracy and conceptual understanding in transferring transactions from journals to ledgers. Over approximately four months, university students collaborated with accounting teachers to design interactive learning strategies, including gradual material presentation, problem-solving exercises, joint discussion of student work, and question-and-answer sessions. This interactive approach proved effective in improving students’ conceptual understanding, active participation, and motivation in learning accounting. On the other hand, university students gained valuable experience in enhancing their communication skills, teaching creativity, and classroom management abilities. Therefore, the teaching assistance activity within the MBKM framework provides a dual contribution, strengthening students’ learning outcomes while preparing university students to become competent future educators and professionals in their respective fields. ABSTRAK Kegiatan asistensi mengajar dalam program Merdeka Belajar Kampus Merdeka (MBKM) merupakan salah satu bentuk implementasi nyata kolaborasi antara perguruan tinggi dan satuan pendidikan. Program ini memberikan kesempatan bagi mahasiswa untuk terlibat langsung dalam proses pembelajaran di sekolah, sehingga siswa dapat mengaplikasikan ilmu yang telah dipelajari sekaligus mengembangkan keterampilan mengajar secara profesional. Kegiatan ini bertujuan untuk meningkatkan kompetensi mengajar mahasiswa serta membantu siswa mengerti materi pelajaran dengan cara yang lebih menarik dan mudah dipahami. Dalam pelaksanaannya, kegiatan asistensi difokuskan pada materi buku besar di kelas XII SMA Santo Kristoforus 2, yang kerap menjadi tantangan bagi siswa karena memerlukan ketelitian dan pemahaman konseptual dalam memindahkan transaksi dari jurnal ke buku besar. Selama kurang lebih empat bulan, mahasiswa berkolaborasi dengan guru akuntansi dalam merancang strategi pembelajaran yang interaktif, seperti pemaparan materi bertahap, latihan soal, pembahasan hasil pekerjaan secara bersama-sama serta sesi tanya jawab. Pendekatan pembelajaran ini terbukti efektif dalam meningkatkan pemahaman konsep, partisipasi aktif, serta motivasi belajar siswa terhadap pelajaran akuntansi. Di sisi lain, mahasiswa memperoleh manfaat dalam mengasah kemampuan komunikasi, kreativitas mengajar, serta manajemen kelas secara langsung. Dengan demikian, kegiatan asistensi mengajar dalam kerangka MBKM memberikan kontribusi ganda, yaitu memperkuat capaian belajar siswa sekaligus mempersiapkan mahasiswa sebagai calon pendidik dan profesional yang kompeten di bidangnya.